DAYA TARIK INFOGRAFIK DALAM MENYAJIKAN BERITA DI MEDIA SOSIAL INSTAGRAM: Studi Kasus Media Online tirto.id - Rizskha Amalia (2020)
Abstract Mass media has an important role in people's lives. This also relates to the fulfillment of information which is increasing. Current technological developments encourage mass media including online media to present news that is concise, fast, and interesting. This study discusses the appeal of infographic in presenting news on Instagram social media. This research was conducted on tirto.id online media. Researchers used a qualitative descriptive method where data was obtained through observation and in-depth interviews. The results of this study indicate that the infographic presented by tirto.id online media on Instagram aims to simplify long writing because tirto.id online media is on the path of data journalism, one of which is infographic. Aside from being a medium for presenting news, infographics are also used as a strategy by the online media tirto.id in order to attract readers with interesting colors and illustrations. The advantage that is highlighted in the tirto.id infographic besides lies in the news content that directly focuses on the core message, then the colors and illustrations in a simple infographic, also filled with accurate data, making the online media tirto.id currently favored by readers. Keywords: Attractiveness, infographics, mass media, online media.